Before the bell - Thorpe, Kiki; Christy, Jana; Disney Enterprises (1996- ) (New York : Random House, 2015)
"It's the first day of school, and Gabby can't wait to tell the fairies all about it. She even met a new friend who loves fairies as much as she does! But what will the Never Girls do when a fairy goes missing in Gabby's new classroom?"--
"A Stepping Stone book"--Cover.
550
Keywords: Fairies -- Fiction; Magic -- Fiction; First day of school -- Fiction; Schools -- Fiction; Friendship -- Fiction